Properties of Functions in the Wiener Class BVp[a, b] for 0<p<1. (6th April 2015) - Niu, Yeli; Wang, Heping
Abstract : We will investigate properties of functions in the Wiener classB V p [ a, b ] with0 < p < 1 . We prove that any function inB V p [ a, b ] ( 0 < p < 1 ) can be expressed as the difference of two increasing functions inB V p [ a, b ] . We also obtain the explicit form of functions inB V p [ a, b ] and show that their derivatives are equal to zero a.e. on[ a, b ] .